2012
DOI: 10.1002/jcb.24354
|View full text |Cite
|
Sign up to set email alerts
|

EPA, an omega‐3 fatty acid, induces apoptosis in human pancreatic cancer cells: Role of ROS accumulation, caspase‐8 activation, and autophagy induction

Abstract: In a recent study, we showed that eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), two common omega-3 fatty acids, can cause ROS accumulation and subsequently induce caspase-8-dependent apoptosis in human breast cancer cells (Kang et al. [2010], PLoS ONE 5: e10296). In this study, we showed that the pancreas has a unique ability to accumulate EPA at a level markedly higher than several other tissues analyzed. Based on this finding, we sought to further investigate the anticancer actions of EPA and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
76
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 54 publications
13
76
1
Order By: Relevance
“…Previously, several reports have suggested a change in autophagy in cancer cell lines that are sensitive and display cytotoxic and/or cytostatic responses to physiological doses of PUFAs. [48][49][50][51][52][53] We explore whether increased autophagy is a part of the cellular response to PUFAs also in spontaneously arising ARPE-19 cells. If so, we hypothesize a correlation between the disease preventive effects of n-3 PUFAs and stimulation of autophagy in retinal pigment epithelial cells where the initial phases of AMD occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, several reports have suggested a change in autophagy in cancer cell lines that are sensitive and display cytotoxic and/or cytostatic responses to physiological doses of PUFAs. [48][49][50][51][52][53] We explore whether increased autophagy is a part of the cellular response to PUFAs also in spontaneously arising ARPE-19 cells. If so, we hypothesize a correlation between the disease preventive effects of n-3 PUFAs and stimulation of autophagy in retinal pigment epithelial cells where the initial phases of AMD occurs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, EPA and DHA reduce the expression of Bcl2 and procaspase-8, and activation of EGFR in human breast cancer cell lines [19]. EPA and DHA induce ROS accumulation in breast and pancreatic cancer cell lines and trigger caspase-8-dependent apoptosis in vitro and in vivo [20,21]. DHA and EPA elevated the expression of the PTEN gene and its protein, peroxisome proliferator-activated receptor gamma (PPARγ), in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…EPA has been considered to inhibit the growth and development of colon, breast and liver cancer and leukemia in vivo and in vitro [18]. Furthermore, many studies have demonstrated that EPA could induce apoptosis in cancer cells and have suggested mechanisms for this biological function [19][20][21].…”
Section: Cardioprotective Effectmentioning
confidence: 99%